2011
DOI: 10.1038/bjc.2011.498
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I inhibition in colorectal cancer: biomarkers and therapeutic targets

Abstract: The topoisomerase I (Top 1) poison irinotecan is an important component of the modern treatment of colorectal cancer. By stabilising Top 1-DNA complexes, irinotecan generates Top 1-linked DNA single-strand breaks that can evolve into double-strand breaks and ultimately cause cell death. However, cancer cells may overcome cell killing by releasing the stalled topoisomerase from DNA termini, thereby reducing the efficacy of Top 1 poisons in clinics. Thus, understanding the DNA repair mechanisms involved in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 53 publications
7
79
0
2
Order By: Relevance
“…This is in agreement with other studies showing a decrease in expression and activity of Topo-1 after treatment with camptothecin or its analogs. 16,35 Our results also showed significantly decreased expression of Topo-1 in patients with longer survival duration as compared to the group with shorter survival duration. These results are not supported by the earlier hypothesis that lower expression of Topo-1 is correlated with a worse response to Topo-1 inhibitors.…”
Section: Numerous Preclinical and Clinical Studies Have Demonstrated supporting
confidence: 68%
See 1 more Smart Citation
“…This is in agreement with other studies showing a decrease in expression and activity of Topo-1 after treatment with camptothecin or its analogs. 16,35 Our results also showed significantly decreased expression of Topo-1 in patients with longer survival duration as compared to the group with shorter survival duration. These results are not supported by the earlier hypothesis that lower expression of Topo-1 is correlated with a worse response to Topo-1 inhibitors.…”
Section: Numerous Preclinical and Clinical Studies Have Demonstrated supporting
confidence: 68%
“…6,11,33,34 It has also been suggested that the cytotoxic effects of these inhibitors are dependent on the stabilization of topoisomerase-DNA complex. 35 Both in vitro and in vivo studies have demonstrated that sensitivity to these agents is modulated by absolute value of Topo-1 levels and Topo-1 protein expression is correlated well with poor patient survival. Our results showed a significant decrease in the expression of Topo-1 in post treatment sections.…”
Section: Numerous Preclinical and Clinical Studies Have Demonstrated mentioning
confidence: 99%
“…Pharmacogenetic and pharmacodynamic markers such as TOP1 have shown limited correlations with free irinotecan response (6,(32)(33)(34). In addition to the intrinsic sensitivity of tumor cells to SN-38, our data indicate that the duration for which tumor cells are exposed to SN-38 (tumor SN-38 duration) also plays a critical role in driving treatment response to irinotecan.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, human U2OS cells are known to undergo premature senescence, demonstrating that this program can be reactivated in these tumor cells (24). SN-38 is the active metabolite of irinotecan, a topoisomerase I inhibitor that is used in the treatment of colorectal cancer (54).…”
Section: Discussionmentioning
confidence: 99%